PRE-SERVICE TEACHERS’ PERFORMANCE POST MICROTEACHING CLASS IN FIELD EXPERIENCE PROGRAM - Putri Dini Meutia; Ferlya Elyza; Yusnila Yusnila (Universitas Islam Negeri Banda Aceh, 2018)
The aim of this study was to investigate the pre-service teachers’ performance in the Field Experience Program after taking a microteaching class. The sample of this study was ten (10) pre-service teachers. The data collected were taken from pre-service teachers’ report books. The results of this study showed that microteaching helped the pre-service teachers in improving and achieving a good teaching performance in classroom during their Field Experience Program. In addition, after the pre-service teachers had a microteaching class, they were able to use appropriate learning methods and classroom management in order to achieve a better performance in the Program. It can be concluded that the microteaching class has played a role to the pre-service teachers in enhancing their teaching performance in the Field Experience Program.